Algorithm of grid reliability assessment and reconstruction optimization system - Zhibin ZANG; Peihao ZHENG; Benhai WEI; Zaipei ZHAI; Shengguo MA (Dianxin kexue)
Based on the research of the reliability of distribution network and the reconstruction of network,a new method was put forward to reconstruct the power grid reliability.Firstly,the evaluation index system was proposed,which included the active network LOSS (LOSS),lack of system power supply (ENS) and the average power supply availability (ASAI).A multi-objective model of distribution network was constructed by normalization,and the multi-objective function was transformed into a new single objective function by using the judgment matrix method,which realized fast calculation of power distribution network reconstruction and optimization.Through IEEE69 example verification,the optimization algorithm can obtain the global optimal solution and reduce the computational time at the same time,effectively solve the problem of the reconstruction of the complex network optimization.